Analysis of a monitoring system for bacterial wilt management by seed potato cooperatives in Ethiopia: Challenges and future directions - Tafesse, S.; Lie, R.; Mierlo, B. van; Struik, P.C.; Lemaga, B.; Leeuwis, Cees (MDPI, 2020)
Collective action is required to deal with various complex agricultural problems such as invasive weeds and plant diseases that pose a collective risk to farmers. Monitoring systems could help to stimulate collective action and avoid free-riding. The paper develops a novel framework consisting of essential elements of a monitoring system for managing a complex disease like bacterial wilt in potato crops. The framework is used to explore how seed potato cooperatives in Ethiopia operationalised the essential elements of a monitoring system and identifies which challenges remain to be overcome. Data were collected through in-depth interviews, reflective workshops, participant observation, and document analysis. We found that the cooperatives had organised a self-monitoring system to monitor disease occurrence and the disease management practices of their members. Monitoring committees were in charge of the data collection and enforcement of sanctions on farmers who did not adhere to the cooperatives’ bylaws. The main challenges included the dependency on visual observation, which does not disclose latent infections, limited financial incentives for the monitoring committee members, lack of trust, weak peer monitoring, and the social and ecological interdependency between producers of ware and seed potatoes. Suggestions are provided to strengthen the monitoring systems of farmers’ seed potato cooperatives in Ethiopia. In addition, we discuss the broader value of our novel framework for describing and analysing monitoring systems for future research and intervention